2011
DOI: 10.1007/s13225-010-0086-5
|View full text |Cite
|
Sign up to set email alerts
|

Community composition of endophytic fungi in Acer truncatum and their role in decomposition

Abstract: The mycota and decomposing potential of endophytic fungi associated with Acer truncatum, a common tree in northern China, were investigated. The colonization rate of endophytic fungi was significantly higher in twigs (77%) than in leaves (11%). However, there was no significant difference in the colonization rates of endophytic fungi between lamina (9%) and midrib (14%) tissues. A total of 58 endophytic taxa were recovered using two isolation methods and these were identified based on morphology and ITS sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(122 citation statements)
references
References 47 publications
(60 reference statements)
6
114
0
2
Order By: Relevance
“…Furthermore, we found that the colonisation rate of endophytic fungi was higher in twigs than in leaves in the four hosts. Similar results were reported in previous studies of mangrove plants (Pang et al 2008; Xing et al 2011) and non-mangrove plants (Fisher et al 1994; Wang and Guo 2007; Sun et al 2011). For example, Xing et al (2011) found that the colonisation rate of endophytic fungi was significantly higher in stem than in leaf in four mangrove Sonneratia species at the south coast of China.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, we found that the colonisation rate of endophytic fungi was higher in twigs than in leaves in the four hosts. Similar results were reported in previous studies of mangrove plants (Pang et al 2008; Xing et al 2011) and non-mangrove plants (Fisher et al 1994; Wang and Guo 2007; Sun et al 2011). For example, Xing et al (2011) found that the colonisation rate of endophytic fungi was significantly higher in stem than in leaf in four mangrove Sonneratia species at the south coast of China.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Phomopsis fungi were widely isolated from mangroves (Suryanarayanan et al 1998; Suryanarayanan and Kumaresan 2000; Pang et al 2008; Xing et al 2011; Xing and Guo 2011) and non-mangrove plants (Taylor et al 1999; Guo et al 2000, 2008; Cannon and Simmons 2002; Murali et al 2006; Sun et al 2011, 2012). In addition, Pestalotiopsis as generalist fungi were common mangrove endophytes and widely occurred on plants across Palmae, Rhizophoraceae, Planchonellae, and Podocarpaceae in China (Liu et al 2010a, 2012; Xing and Guo 2011; Gong et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One sampled P. deltoides (Morse, AP1) tree achieved the highest abundance of C. radians, a member of Phylum Basidiomycota (91.8% of relative frequency), and the lowest abundance of members of the Phylum Ascomycota (8.2%). This fungus may have been present as an endophyte or a wood-decaying species prior to the insect attack (Eslyn and Lombard 1984;Sun et al 2011). The results obtained during this study complement the previous data reported by Ceriani-Nakamurakare et al (2016) representing the first comprehensive analyses on fungal communities associated to M. mutatus.…”
Section: Discussionsupporting
confidence: 79%
“…In the case of symbiotic association there is an increase in biomass as well as better development of aerial parts (Das et al, 2012). They are important components of the plant micro-ecosystem (Rodriguez et al, 2009;Zhang et al, 2006;Tan and Zhou, 2001) and are ubiquitous, colonize all plants and have been isolated from mosses (Davey and Currah, 2006), lichens (Li et al, 2007 a,b;Suryanarayanan et al, 2005) shrubs (Petrini et al, 1982), ferns (Swatzell et al, 1996), grasses (Muller and Krauss, 2005;Su et al, 2010), coniferous trees (Sun et al, 2011;Albrectsen et al, 2010;Mohamed et al, 2010). In the long co-evolution of the endophytes and their host plant, the endophytes have adapted themselves to the microenvironment by genetic variation including uptake of some plant DNA into their own genome.…”
Section: Introductionmentioning
confidence: 99%